Morphological similarity and graphological difference - Kipouràs, Pàvlos (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The Document Examiner’s approach could not be based only on the technical aspect of the analysis, but it must very often be extended in the graphological analysis of the case. The Document Examiner has to also take into consideration the particular historical data in order to orientate the investigation’s hypothesis. In many cases morphological similarity could be tricky and misleading, just because of the simplefact that reflects the main purpose of the forger: the similarity, in which he bases the effort of presenting a forged document genuine.
Keywords: pismo odręczne; przeciwieństwo; personalizacja; tendencja; zbieg okoliczności; biegły; różnice grafologiczne; podobieństwa morfologiczne